Lαp -boundedness of the pseudo-differential operators associated with the Kontorovich–Lebedev transform - Srivastava H.M.; Chauhan M.S.; Upadhyay S.K. (My University, 2025)
In this article, the authors prove a potentially useful Lαp-boundedness result for the pseudo-differential operators involving the Kontorovich–Lebedev transform. Several other related recent investigations, which dealt with the Kontorovich–Lebedev transform and the pseudo-differential operators are also considered for motivation purposes. © 2020, The Royal Academy of Sciences, Madrid.